PEMBELAJARAN PENDIDIKAN MULTIKEAKSARAAN DENGAN TEMA KESEHATAN DAN OLAH RAGA PADA KOMUNITAS SUKU DAYAK - Nunung Nurazizah (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2017)
Implementation of multi-literacy education in Dayak ethnic community is still not accordance with the Regulation of the Minister of Education and Culture of Republic of Indonesia number 42 in 2015. The objective of this research is to develop a syllabus and learning materials on multi-literacy learning toward Dayak indigenous community as a target. Research methods used are research and development. The research was conducted from August to October 2016. It was also conducted in PKBM Bintang Timur Kabupaten Barito Utara and PKBM Mawar Merah Kabupaten Kapuas. Results show that multi-literacy learning materials are useful for tutors to deliver multi-literacy educational materials in accordance with a curriculum, and as a tool for learners to master the materials delivered by tutors. It is expected that the impact of the syllabus and learning materials implementation can escalate learners’ multi-literacy abilities and behavior changes in maintaining environment.